PENTNGKATAN KETERAMPILAN INDUSTRI PRODUK FIBERGLASS DI CV JAMINDO SEJAHTERA JOGYA - Siswantoyo, Siswantoyo; Sudarko, Rumpis Agus (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2005)
Smallindustrialoftenalsoreferredwiththe smallindustryowning.,.ideof rolewhen seenfromtrilogyofIndonesiadevelopment.Small-:dustrialattendancefromtimeto timehave earnedtogivetheevidencein.'.::coming emulationand abilitytolinger.Especialaspecthad by small.:Justrynamelymotivateand flexibility.Attendance ofthisinterpreneurshipsProgrammeisvery assistingto:: morepreparethenew candidatebusinessmanas accordingtoarea::'. eloped. Target of thisactivityfor exampleimprovingstudentknowledge.. :he rvorldofinterpreneurshipin areafiberglass,skilledproduce, peeping. -: idea desaign ofrelatedto its sciencearea.Amountofparticipant10,::Jent, This activit-visconductedby counted3 timesperr"'eeksduring5:. . nth. MagangF'iberglassrepresentone ofthesolutionconcept tosupply..-.:student so thatcan createthework fieldandcanviewith the other.Wirat.:rnallyexpectedcanaim tothe sportofequipmentandsport industry.l.fierials usedfor thefiberglassoffor example: resin,katalist, Med,-,-balt.Talc in and Outside,clay,was,powdergip, paint,etc. Basically-:uldused canbe madeof assortedis whichis forexample;mould once:=..topieces,Mouldtwicefall topieces,andmouldsiliconAddedvaluetoparticipant for examplemountingknowledgeand:s:iledproduce the fiberglass.AddedValue toPartnerIndustry, existenceof- .,-rperation braidwith thecollegeand strengthenthe reference ofbranch:.iEessociety andalsoopened byopportunityofproductiondevelopmenthavebackgroundto athleticscienceareaand health byvarious:-,.elopmentofappliance ofathleticfacilityandphysic.Constraint facedby.:.rch --.:l'leld forexample,the collidingoftimemagangwith the lecturing and=.so the happeningofpricechangeofraw materialwhichexcelsior.Sothat: rnceptionthe efficiencyand effectivenessinthisactivityprogramisvery::id attention.Xe1' words:interpreneurship, liber glass'andsport